The LYMPH trial: comparing microsurgical with conservative treatment for chronic breast cancer-associated lymphoedema – study protocol of a pragmatic randomised international multicentre superiority trial - Andrea L Pusic; Matthias Schwenkglenks; Karin Ribi; Jane Shaw; Shan Shan Qiu; Walter Weber; Martin Halle; Khalil Zaman; Raymund E Horch; Marco Cattaneo; Cristina Granziera; Elisabeth A Kappos; et al. (BMJ Open, 2025)
Introduction Up to one-fifth of breast cancer survivors will develop chronic breast cancer-related lymphoedema (BCRL). To date, complex physical decongestion therapy (CDT) is the gold standard of treatment. However, it is mainly symptomatic and often ineffective in preventing BCRL progression. Lymphovenous anastomosis (LVA) and vascularised lymph node transfer (VLNT) are microsurgical techniques that aim to restore lymphatic drainage. This international randomised trial aims to evaluate advantages of microsurgical interventions plus CDT versus CDT alone for BCRL treatment.Methods and analysis The effectiveness of LVA and/or VLNT in combination with CDT, which may be combined with liposuction, versus CDT alone will be evaluated in routine practice across the globe. Patients with BCRL will be randomly allocated to either surgical or conservative therapy. The primary end point of this trial is the patient-reported quality of life (QoL) outcome ‘lymphoedema-specific QoL’, which will be assessed 15 months after randomisation. Secondary end points are further patient-reported outcomes (PROs), arm volume measurements, economic evaluations and imaging at different time points. A long-term follow-up will be conducted up to 10 years after randomisation. A total of 280 patients will be recruited in over 20 sites worldwide.Ethics and dissemination This study will be conducted in compliance with the Declaration of Helsinki and the International Council for Harmonisation-Good Clinical Practice (ICH-GCP) E6 guideline. Ethical approval has been obtained by the lead ethics committee ‘Ethikkommission Nordwest- und Zentralschweiz’ (2023-00733, 22 May 2023). Ethical approval from local authorities will be sought for all participating sites. Regardless of outcomes, the findings will be published in a peer-reviewed medical journal. Metadata detailing the dataset’s type, size and content will be made available, along with the full study protocol and case report forms, in public repositories in compliance with the Findability, Accessibility, Interoperability and Reuse principles.Trial registration number NCT05890677.